The Rediscovery of Wisdom - Conway, D. author. aut Link
X, 196 p.
Keywords: By reconstructing it and tracing its vicissitudes, David Conway rehabilitates a time-honoured conception of philosophy, originating in Plato and Aristotle, which makes theoretical wisdom its aim. Wisdom is equated with possessing a demonstrably correct understanding of why the world exists and has the broad character it does. Adherents of this conception maintained the world to be the demonstrable creation of a divine intelligence in whose contemplation supreme human happiness resides. Their claims are defended against various latter-day scepticisms.